Production of formate by CO2 electrochemical reduction and its application in energy storage. Issue 1 (9th December 2019) - Xiang, Hang; Miller, Hamish Andrew; Bellini, Marco; Christensen, Henriette; Scott, Keith; Rasul, Shahid; Yu, Eileen H.
Abstract : Formate as a medium for CO2 utilisation and energy storage. Abstract : Production of liquid fuels by electrochemical CO2 reduction (eCO2 R) is an attractive option for energy storage in the form of renewable energy. This study focuses on efficient formate production using an eCO2 R system and its application in generating power using a direct formate fuel cell (DFFC). A carbon black supported SnO2 catalyst was used for the eCO2 R in a gas diffusion reactor using a 1.0 M KOH electrolyte. An average faradaic efficiency of 80% for formate production was achieved over a wide electrode potential range (−0.63 to −1.43 V vs. RHE). Since the overall current density varied linearly with the overpotential, the rate of formate production could be easily controlled by varying the applied potential. At a current density of 251 mA cm −2 (−1.43 V), a high formate production rate was achieved at 3 mg min −1 cmWE −2 resulting in 0.5 M formate being produced within 1 hour. This formate solution was directly used as the fuel for a DFFC, without pre-treatment. The fuel cell consisted of a Pd–CeO2 /C anode and FeCo/C cathode and produced a peak power density of 92 mW cm −2 . A closed loop of "electricity–formate–electricity" has been realized in this study, signifying the promising future of sustainable CO2 conversion to liquid fuels for CO2 fixation as well as for energy storage.